2001
DOI: 10.1038/sj.gt.3301488
|View full text |Cite
|
Sign up to set email alerts
|

Efficient infection of primitive hematopoietic stem cells by modified adenovirus

Abstract: Almost all studies of adenoviral vector-mediated gene transfer have made use of the adenovirus type 5 (Ad5). Unfortunately, Ad5 has been ineffective at infecting hematopoietic progenitor cells (HPC). Chimeric Ad5/F35 vectors that have been engineered to substitute the shorter-shafted fiber protein from Ad35 can efficiently infect committed hematopoietic cells and we now show highly effective gene transfer to primitive progenitor subsets. An Ad5GFP and Ad5/F35GFP vector was added to CD34 + and CD34 − lineage − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 55 publications
(43 reference statements)
2
84
1
Order By: Relevance
“…One candidate target cell for Ad-BMP2 could be nucleated cells of the peripheral blood. We 24 and others 25 have demonstrated the suitability of Ad5F35 vectors, unlike Ad5 vectors, to transduce efficiently human hematopoietic cells.…”
Section: Discussionmentioning
confidence: 92%
“…One candidate target cell for Ad-BMP2 could be nucleated cells of the peripheral blood. We 24 and others 25 have demonstrated the suitability of Ad5F35 vectors, unlike Ad5 vectors, to transduce efficiently human hematopoietic cells.…”
Section: Discussionmentioning
confidence: 92%
“…Both others and we have shown that Ad vectors containing the Ad35 fiber or fiber knob (Ad5/35) efficiently transduce human and non-human primate HSPCs in vitro. [7][8][9][10] Integration site analysis Genomic DNA was isolated from GFP 1 hCD46tg colonies using the DNeasy Blood and Tissue Kit (Qiagen, Valencia, CA). These CFU colonies were obtained from Lin 2 /GFP 1 BM cells of in vivo transduced hCD46tg animals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Ad5/35 vectors efficiently infect human CD34 + cells, particularly subsets with potential stem cell activity. For example, at an MOI of 10pfu/cell, Ad5/35 transduced the majority of CD34 + /c-Kit + [4], CD34 + /CD38 -, CD34 -/Lin -, and Hoechst 33342 dye-negative side population (SP) cells [6]. Furthermore, Ad5/35 vectors allowed for efficient gene transfer into non-dividing CD34 + cells [7], which is important as most of the repopulating HSCs are quiescent.…”
Section: Introductionmentioning
confidence: 99%